2007
DOI: 10.1186/1749-799x-2-26
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal-analgesia for pain management after Hallux Valgus surgery: a prospective randomised study on the effect of ankle block

Abstract: Background: Pain and emesis are the two major complaints after day case surgery. Local anaesthesia has become an important part of optimizing intra and post-operative pain treatment, but is sometimes not entirely sufficient. The aim of the present study was to study the effect of adding an ankle block to a multi-modal analgesic approach on the first 24-hour-need for rescue analgesia in patients undergoing elective Hallux Valgus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 15 publications
2
34
0
7
Order By: Relevance
“…18 Bupivacaine ankle block can reduce the need for rescue analgesia compared to the lidocaine block. 38 Postoperative pain can be amplified by central neuroplasticity due to operative nociception. 10 Preemptive analgesia is an antinociceptive treatment that prevents establishment of altered central processing of afferent input from the site of injury/surgery.…”
Section: Discussionmentioning
confidence: 99%
“…18 Bupivacaine ankle block can reduce the need for rescue analgesia compared to the lidocaine block. 38 Postoperative pain can be amplified by central neuroplasticity due to operative nociception. 10 Preemptive analgesia is an antinociceptive treatment that prevents establishment of altered central processing of afferent input from the site of injury/surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In HV correction surgery however, surgeons may be bothered by the edema of soft tissues around the surgical site after preoperative peri‐incisional LA infiltration that might disturb recognition of anatomic structures. In addition, peri‐incisional LA infiltration alone showed less analgesic effect than combined ankle nerve blocks with LA infiltration due to peri‐incisional LA infiltration not being able to anesthetize the medial first metatarsal bone that is innervated by deep peroneal and medial plantar nerves. It elucidates that the lesser analgesic effect of LA administration as compared with ankle blocking in this study might be due to the lack of blockade of the deep layer nerve distributions on periosteum.…”
Section: Discussionmentioning
confidence: 99%
“…The tibial nerve innervates the volar aspect of foot, and there are many sites capable of blocking it. It can be blocked by using a classic or sustentaculum tali approach via injection of LA below the medial malleolus or just anatomically posterior to the medial malleolus parallel to posterior tibial artery . However, via using ultrasound guidance to assist peripheral nerve blockade, the technique became more successful than traditional landmark or nerve stimulation and the block needle is able to penetrate the flexor hallucis longus muscle above the tip of medial malleolus without palpation of artery pulsation .…”
Section: Discussionmentioning
confidence: 99%
“…In their prospective study of 71 cases, Russell et al [2] reported that ankle block markedly decreased the postoperative 24-h VAS score and that it is a safe method. On the contrary, Turan et al [15] performed preincisional local lidocaine with general anesthesia in 90 cases and found no effect of adjuvant ankle block on acute surgical pain. In their study, etoricoxib and paracetamol were administered as the standard analgesic treatment, and no difference was detected between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The aim was only to assess the efficacy of ankle block as an adjuvant to general anesthesia. Turan et al [15] found that the ankle block group had markedly lower 24-h VAS scores. Paracetamol and tramadol were used for the postoperative analgesic regimen.…”
Section: Discussionmentioning
confidence: 99%